Patterns of adverse childhood experiences and depressive symptom trajectories in young adults: A longitudinal study of college students in China - Li, Shuqin; Wang, Rui; Thomas, Erica; Jiang, Zhicheng; Jin, Zhengge; Li, Ruoyu; Qian, Yan; Song, Xianbing; Sun, Ying; Zhang, Shichen; Chen, Ruoling; Wan, Yuhui (Frontiers in Psychiatry, 2022)
Background Adverse childhood experiences (ACEs) tend to cluster together in daily life, and most studies focus on the level of depression at certain points, but the dynamic process of depression is often neglected. Thus, research is urgently needed to explore the relationship between ACEs pattern and trajectory of depressive symptom levels at multiple time points in order to provides early targeted interventions to those who are most at risk. Objective We aimed to explore patterns of ACEs, including types and timing, associated with depression trajectories in college students. Methods A school-based health survey was used to collect data as part of a longitudinal study in two medical college in Anhui province, China. Questionnaires were issued to 3,662 participants aged 17–22 and recorded details of ACEs (types and timing) and depression. Latent class analysis (LCA) was used to identify “patterns” of ACEs type and timing. Depressive symptom trajectories employed latent class growth analysis (LCGA). Multiple logistic regressions were employed to evaluate the relationships between ACEs patterns and depressive symptom trajectories. Results We identified five ACEs patterns: “High neglect/emotional abuse/community violence,” “High neglect/emotional abuse,” “High neglect/family dysfunction,” “High neglect,” “Low ACEs.” We traced three depression trajectories: “High depressive symptom” “Moderate depressive symptom,” “Low depressive symptom.” “High neglect/emotional abuse/community violence,” “High neglect/emotional abuse” and “High neglect/family dysfunction” demonstrated a high risk for “High depressive symptom” and “Moderate depressive symptom.” “High neglect” showed a high risk for “Moderate depressive symptom” but not for “High depressive symptom” (P < 0.05). Conclusions The findings address the need for a comprehensive consideration of exposure to childhood adversity associated with the risk of depression in young adults through identifying more problematic ACEs patterns amongst exposed children.